2019
DOI: 10.1002/ange.201910510
|View full text |Cite
|
Sign up to set email alerts
|

A Plasma‐Triggered O−S Bond and P−N Junction Near the Surface of a SnS2 Nanosheet Array to Enable Efficient Solar Water Oxidation

Abstract: Ap hotoelectrochemical (PEC) cell can split water into hydrogen and oxygen with the assistance of solar illumination. However,i ts application is still limited by excessive bulk carrier recombination and sluggish surface oxygen evolution reaction (OER) kinetics.T aking SnS 2 as an example,apromising layered optoelectronic semiconductor, Ar plasma treatment strategy was used to introduce aSnS/SnS 2 PÀNheterojunction and OÀSbond near the surface of aSnS 2 nanosheet array,s imultaneously increasing the separation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
0
5
0
Order By: Relevance
“…n photoelectrochemical (PEC) water splitting, the oxygen evolution reaction (OER) is considered to be the rate-limiting step compares to its hydrogen evolution counterpart reaction. This is because OER has four electron transferring processes along with complexities in the coupled ion and photogenerated electron/hole transport mechanism near the photoanode surface [1][2][3][4][5] . As a result, a better understanding of the interactions between ions in the electric double layer and charge carriers in the few atomic layers at the anode surface is critical for developing efficient PEC cells [6][7][8] .…”
mentioning
confidence: 99%
“…n photoelectrochemical (PEC) water splitting, the oxygen evolution reaction (OER) is considered to be the rate-limiting step compares to its hydrogen evolution counterpart reaction. This is because OER has four electron transferring processes along with complexities in the coupled ion and photogenerated electron/hole transport mechanism near the photoanode surface [1][2][3][4][5] . As a result, a better understanding of the interactions between ions in the electric double layer and charge carriers in the few atomic layers at the anode surface is critical for developing efficient PEC cells [6][7][8] .…”
mentioning
confidence: 99%
“…In conformity with XPS results, we argue that the p–n junction forms due to the fractional Sn 4+ → Sn 2+ conversion in the presence of V S , which induces a pseudo-p-type SnS layer over the SnS 2 surface . Other published reports have also established the existence of a p–n homojunction in SnS 2 via the M–S plot. , Given that we carried out hydrogen evolution (HER) at the electrode–electrolyte interface, we contend that the p–n junction obtained from the Mott–Schottky plot supports the homojunction and relates to our HER findings. From the flat band potential determination in all three electrolytes (Table S5a–c), we have found that relative to S3, the excess sulfur vacancies in S10 cause a shift in the n-type Fermi level ( E fn ) to a more negative value and the p-type Fermi level ( E fp ) to a more positive value, with an increase in both donor and acceptor type densities.…”
Section: Resultsmentioning
confidence: 99%
“…The values of Rs, R p1 , and R p2 are summarized in Table S1. The smaller R p2 of the Fh/WO 3 under light irradiation suggests the fast water oxidation kinetics [35]. To confirm the charge separation effect after decorating the Fh, the charge separation efficiencies in the bulk (η bulk ) and on the surface (η surface ) were investigated in a buffer solution (see the ESI † for calculation details) [36].…”
Section: Photoelectrochemical Properties Of the Fabricated Photoanodesmentioning
confidence: 99%